2012
DOI: 10.1016/j.medin.2011.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Estudio ECAIS: eventos cardiovasculares adversos inadvertidos en sepsis

Abstract: PALABRAS CLAVEIsquemia miocárdica; Electrocardiografía ambulatoria; Sepsis; Choque séptico Resumen Objetivo: Describir la incidencia de eventos cardiovasculares adversos en pacientes con diagnóstico de sepsis en sus diferentes estadios. Diseño: Estudio observacional, descriptivo, longitudinal. Ámbito: Unidades de cuidados intensivos de tipo mixto de dos hospitales universitarios en la ciudad de Bogotá. Participantes: Se incluyeron una serie de pacientes mayores de edad, que ingresan a UCI con diagnostico de se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
1
9
1
Order By: Relevance
“…Unlike the study by Duke et al[13], in ours, HRV parameters were significantly different between survivors and nonsurvivors only in the 20-minute Holter. Holter with shorter periods of record is potentially more useful for be used in critical care patients, including those with sepsis, because these patients present immediate risk of death and therefore need a fast tool for definition of severity.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Unlike the study by Duke et al[13], in ours, HRV parameters were significantly different between survivors and nonsurvivors only in the 20-minute Holter. Holter with shorter periods of record is potentially more useful for be used in critical care patients, including those with sepsis, because these patients present immediate risk of death and therefore need a fast tool for definition of severity.…”
Section: Discussioncontrasting
confidence: 99%
“…Global HRV parameters such as SDNN and TP were lower in nonsurviving patients of this study, which is consistent with the findings of previous studies[12, 13]. Chen et al[12] had demonstrated that SDNN would be a significant independent variable in the prediction of in-hospital mortality for emergency department patients with sepsis, although these authors did not present cut-off point for this HRV parameter.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“… 18/61 Prospective bedside detection +12-lead confirmation n/a Moderate Christian et al ., 2008 [ 17 ] Single center, mixed ICU, USA. 274/274 Retrospective review of monitor data from a database developed for benchmarking Death Moderate Gomez et al ., 2012 [ 18 ] Multicenter, mixed ICUs, Columbia. 100/100 Prospective detection using telemetry n/a Low Goodman et al ., 2007 [ 19 ] Single center, mixed ICU, Israel.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the reported incidences in our review varied widely between studies, which may be explained by random variation due to the small sample sizes of most included studies, but also by differences in patient populations and by misclassification (that is, not all episodes of AF may have been correctly detected). In fact, the domain was not clearly defined in five studies, and some did not explicitly exclude patients who developed sepsis following cardiac surgery [ 18 , 22 - 24 , 26 ]. In addition, another seven studies did not explicitly exclude patients with a prior history of chronic or paroxysmal AF [ 16 , 18 , 21 - 24 , 26 ].…”
Section: Discussionmentioning
confidence: 99%